Protection of Intellectual Property and its Economic Aspects - Pelegrinová, Lenka; Lačný, Martin (Journal of Economic Development, Environment and People, 2016)
Intellectual property as assets in intangible form is classified in most countries under the definitions of the TRIPS Agreement and PCT according to the manner of its protection. This article presents results of an analysis of relationship between the protection of intellectual property rights at certain globalization level and verification of their influence on economic indicators in the selected countries of the research sample – 32 countries of a similar intellectual property protection system under the PCT. An examination of the level of globalization as a quantitative marker was enabled by the KOF Index of Globalization. The time and cross-sectional data enabled to test 352 objections by applying a non-parametric statistical method – panel data regression with the effect of random cross-sectional variables. The conclusions show that there is a statistically significant probability of the relation between the quantity of registered patents and the level of gross domestic product, gross domestic product per capita and adjusted net national income.